2014
DOI: 10.1111/dme.12482
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of gestational diabetes in obese pregnant women from the UK Pregnancies Better Eating and Activity (UPBEAT) pilot trial

Abstract: A combination of routinely measured clinical factors and adiponectin measured in the early second trimester in obese women may provide a useful approach to the prediction of gestational diabetes. Validation in a large prospective study is required to determine the usefulness of this algorithm in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 30 publications
3
43
1
Order By: Relevance
“…Attempts directed towards early detection of GDM using the classical method of ELISA have identified adiponectin[60], free fatty acids[61], sex hormone binding globulin (SHBG) and placental growth hormone[62] as promising biomarkers. In a pilot trial, using biochemical analyses and ELISA,Maitland et al (2014) examined a large number of serum biomarkers related to insulin resistance in obese women for prediction of GDM in the early second trimester. They concluded that a combination of routinely measured clinical factors and adiponectin measured in the early second trimester in obese women holds promise as useful predictors of GDM[63].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts directed towards early detection of GDM using the classical method of ELISA have identified adiponectin[60], free fatty acids[61], sex hormone binding globulin (SHBG) and placental growth hormone[62] as promising biomarkers. In a pilot trial, using biochemical analyses and ELISA,Maitland et al (2014) examined a large number of serum biomarkers related to insulin resistance in obese women for prediction of GDM in the early second trimester. They concluded that a combination of routinely measured clinical factors and adiponectin measured in the early second trimester in obese women holds promise as useful predictors of GDM[63].…”
mentioning
confidence: 99%
“…In a pilot trial, using biochemical analyses and ELISA,Maitland et al (2014) examined a large number of serum biomarkers related to insulin resistance in obese women for prediction of GDM in the early second trimester. They concluded that a combination of routinely measured clinical factors and adiponectin measured in the early second trimester in obese women holds promise as useful predictors of GDM[63]. Another group, using biochemical…”
mentioning
confidence: 99%
“…In a study including 90 women who developed GDM, Rasanen et al have reported AUC of 0.91 between 5 and 13 weeks of gestation with a single marker, glycosylated fibronectin, but these results will have to be replicated in larger studies [45]. Finally, with a model including clinical factors and adiponectin measured between 15 and 17 weeks, Maitland et al obtained an AUC of 0.83 in a recent study including 117 obese pregnant women [46]. In line with these studies with less conventional biomarkers, our models improve the capability to identify early in pregnancy women at risk of developing GDM and in particular those who will require insulin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…On further application of regression analysis to develop a prediction model, the area under the receiver-operating curve was 0.713 for maternal risk factors alone which showed a significant change when anterior abdominal skin fold The UK Pregnancies Better Eating and Activities Trials (UPBEAT) study, suggested a limited potential role for taking detailed maternal anthropometry as an aid to gestational diabetes prediction [35]. The UPBEAT trial had assessed;…”
Section: Discussionmentioning
confidence: 99%
“…Skin-fold thickness at the biceps, triceps, sub-scapular and supra-iliac region [35] but failed to also examine the abdominal skin fold thickness.…”
Section: Discussionmentioning
confidence: 99%